A Evaluating Teacher-Student Interaction and the Implementation of Sociomathematical Norms in Indonesian Mathematics Classrooms - Eka Fitria Ningsih; Wawan Wawan; Ardi Dwi Susandi (Journal of Transdisiplinary Studies in Education, 2025)
Background: Teacher-student interaction plays a pivotal role in shaping the quality of mathematics learning. However, in many Indonesian classrooms, traditional models of instruction often dominate, limiting opportunities for students to engage in meaningful mathematical discourse. Aims: This study aims to: (1) evaluate the patterns of teacher-student interaction during mathematics instruction in Indonesian secondary schools, and (2) examine the implementation of sociomathematical norms in a redesigned learning model using a problem-posing approach. Methods: A qualitative research approach was adopted involving observations of eight mathematics classrooms in Lampung, Indonesia. During the odd semester, four classes were observed using conventional teaching methods. In the even semester, four teachers implemented a problem-posing model co-designed with the researcher. Data were collected via classroom video recordings and analyzed using the Flanders Interaction Analysis System (FIAS) with support from NVIVO software. Results: The findings reveal that traditional classrooms were heavily teacher-dominated, with 86% of classroom talk attributed to teachers and only 14% to students. Common classroom norms included praying, singing, asking questions, listening to explanations, and discussions. In contrast, problem-posing classrooms demonstrated the emergence of sociomathematical norms such as mathematical explanation, differentiation of ideas, and student-generated problems. Conclusion: The study highlights the limited interaction in traditional classrooms and the potential of sociomathematical norms to enrich student participation and mathematical discourse when implemented through structured problem-posing models. These findings inform future instructional design that prioritizes interactive and student-centered learning environments in mathematics education.